Waist circumference a good indicator of future risk for type 2 diabetes and cardiovascular disease - Siren Reijo; Eriksson Johan G; Vanhanen Hannu (BMC Public Health, 2012)
Abstract Background Abdominal obesity is a more important risk factor than overall obesity in predicting the development of type 2 diabetes and cardiovascular disease. From a preventive and public health point of view it is crucial that risk factors are identified at an early stage, in order to change and modify behaviour and lifestyle in high risk individuals. Methods Data from a community based study was used to assess the risk for type 2 diabetes, cardiovascular disease and prevalence of metabolic syndrome in middle-aged men. In order to identify those with increased risk for type 2 diabetes and/or cardiovascular disease sensitivity and specificity analysis were performed, including calculation of positive and negative predictive values, and corresponding 95% CI for eleven different cut-off points, with 1 cm intervals (92 to 102 cm), for waist circumference. Results A waist circumference ≥94 cm in middle-aged men, identified those with increased risk for type 2 diabetes and/or for cardiovascular disease with a sensitivity of 84.4% (95% CI 76.4% to 90.0%), and a specificity of 78.2% (95% CI 68.4% to 85.5%). The positive predictive value was 82.9% (95% CI 74.8% to 88.8%), and negative predictive value 80.0%, respectively (95% CI 70.3% to 87.1%). Conclusions Measurement of waist circumference in middle-aged men is a reliable test to identify individuals at increased risk for type 2 diabetes and cardiovascular disease. This measurement should be used more frequently in daily practice in primary care in order to identify individuals at risk and when planning health counselling and interventions.